The Impact of Juvenile Sex Offending on the Adult Criminal Career. (June 2020) - Reale, Kylie; McCuish, Evan; Corrado, Raymond
Although past studies demonstrated the heterogeneity of the criminal career patterns of juveniles with sexual offenses (JSOs), such studies did not directly assess whether JSOs have different adult offending outcomes compared with juvenile nonsex offenders. Using data on a subsample of males from the Incarcerated Serious and Violent Young Offender Study, JSOs ( n = 78), juveniles with violent offenses (JVOs; n = 550), and juveniles with nonviolent offenses (JNVOs; n = 281) were compared across a variety of adult offending outcomes. JSOs were not associated with a specific trajectory of general offending in adulthood, nor were they associated with a range of adult criminal career parameters (e.g., frequency, severity, specialization, and versatility). However, a range of other indicators of juvenile offending were associated with general offending in adulthood. For juvenile males who experience incarceration, many elements of their offending history mattered for adult offending outcomes, but not sexual offending. Policy implications for treatment and management are discussed.